FRI0030 MORE THAN HALF OF NEWLY DIAGNOSED RA PATIENTS ARE NOT CONVINCED OF THE NECESSITY OF RA MEDICINES: ASSOCIATIONS WITH RA CHARACTERISTICS, SYMPTOMS, AND FUNCTION IN THE CANADIAN EARLY ARTHRITIS COHORT (CATCH). (2nd June 2020) - Ta, V.; Schieir, O.; Valois, M. F.; Hazlewood, G.; Hitchon, C.; Bessette, L.; Tin, D.; Thorne, C.; Pope, J.; Boire, G.; Keystone, E.; Bykerk, V.; et al.
Abstract : Background: Although DMARDs are essential for early aggressive control of RA to reduce symptoms and disability, medication adherence is variable. Beliefs about the necessity of medications and safety concerns predict adherence and are modifiable. Objectives: To examine associations among RA medication necessity beliefs and concerns, sociodemographics, RA characteristics, symptom level and function in newly diagnosed RA patients. Methods: Baseline data were analyzed from participants in the Canadian Early Arthritis Cohort (CATCH) who enrolled between 2017-2020 and completed the Beliefs about Medicine Questionnaire (BMQ) and PROMIS-29. All met ACR1987 or 2010 ACR/EULAR criteria and had active RA at enrollment. BMQ Necessity (N) and Concerns (C) scores were classified as high (≥20) or low (<20) and categorized into: Accepting (↑N ↓C); Ambivalent (↑N↑C); Sceptical (↓N↑C); and 4) Indifferent (↓N↓C). Groups were compared using ANOVA and chi-square tests. Results: The 362 patients were mostly white (83%) women (66%) with a mean (SD) age of 56 (15), symptom duration of 6 (3) months, and 32% were obese (BMI≥30). More than half (56%) were DMARD-naive or minimally exposed. Mean N and C scores were similar between men and women; 54% were classified as Indifferent, 31% Accepting, 9% Ambivalent, and 6% Sceptical . As compared to those classified as Accepting, more Indifferent participants smoked, had a healthy weight, lower TJCs, and trend for lower CDAI (Table). Groups were similar by sociodemographics, symptom duration, and DMARD/steroid use, except fewer Indifferent patients received MTX. Indifferent patients had statistically and meaningfully lower patient global, depression, anxiety, fatigue and pain interference, and higher function and participation scores (Table). Conclusion: Many new RA patients had low medication necessity beliefs and concerns, and only 31% had high necessity beliefs and low concerns around diagnosis. Lifestyle and lower CDAI, TJCs, symptoms and functional impacts were associated with RA medication indifference. Identifying medication indifference can prompt discussions about medication beliefs/concerns to facilitate shared decision-making and adherence. Disclosure of Interests: Viviane Ta: None declared, Orit Schieir: None declared, Marie-France Valois: None declared, Glen Hazlewood: None declared, Carol Hitchon Grant/research support from: UCB Canada; Pfizer Canada, Louis Bessette Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer, Roche, Sanofi, UCB Pharma, Consultant of: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer, Roche, Sanofi, UCB Pharma, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer, Sanofi, Diane Tin: None declared, Carter Thorne Consultant of: Abbvie, Centocor, Janssen, Lilly, Medexus/Medac, Pfizer, Speakers bureau: Medexus/Medac, Janet Pope Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lilly & Company, Merck, Roche, Seattle Genetics, UCB, Consultant of: AbbVie, Actelion, Amgen, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Eicos Sciences, Eli Lilly & Company, Emerald, Gilead Sciences, Inc., Janssen, Merck, Novartis, Pfizer, Roche, Sandoz, Sanofi, UCB, Speakers bureau: UCB, Gilles Boire Grant/research support from: Merck Canada (Registry of biologices, Improvement of comorbidity surveillance) Amgen Canada (CATCH, clinical nurse) Abbvie (CATCH, clinical nurse) Pfizer (CATCH, Registry of biologics, Clinical nurse) Hoffman-LaRoche (CATCH) UCB Canada (CATCH, Clinical nurse) BMS (CATCH, Clinical nurse, Observational Study Protocol IM101664. SEROPOSITIVITY IN A LARGE CANADIAN OBSERVATIONAL COHORT) Janssen (CATCH) Celgene (Clinical nurse) Eli Lilly (Registry of biologics, Clinical nurse), Consultant of: Eli Lilly, Janssen, Novartis, Pfizer, Speakers bureau: Merck, BMS, Pfizer, Edward Keystone Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, F. Hoffmann-La Roche Inc, Gilead, Janssen Inc, Lilly Pharmaceuticals, Pfizer Pharmaceuticals, Sanofi-Aventis, Consultant of: AbbVie, Amgen, AstraZeneca Pharma, Biotest, Bristol-Myers Squibb Company, Celltrion, Crescendo Bioscience, F. Hoffmann-La Roche Inc, Genentech Inc, Gilead, Janssen Inc, Lilly Pharmaceuticals, Merck, Pfizer Pharmaceuticals, Sandoz, UCB., Speakers bureau: Amgen, AbbVie, Bristol-Myers Squibb Canada, F. Hoffmann-La Roche Inc., Janssen Inc., Merck, Pfizer Pharmaceuticals, Sanofi Genzyme, UCB, Vivian Bykerk: None declared, Susan J. Bartlett Consultant of: Pfizer, UCB, Lilly, Novartis, Merck, Janssen, Abbvie, Speakers bureau: Pfizer, UCB, Lilly, Novartis, Merck, Janssen, Abbvie